Implementation of the Mind Mapping Method in Improving Memorizing of Al-Quran Verses at MI Faqihul Ilmi - Said, Kurnia (MANDAILING GLOBAL EDUKASIA, 2025)
Improving the quality of learning the Qur'an is a major concern in Islamic education, especially in the memorization aspect. Effective learning methods are needed to help students memorize the verses of the Qur'an more easily and enjoyably. One method that can be applied is mind mapping, which connects the main concepts in the form of mind map visualization. This study aims to analyze the application of the mind mapping method in improving memorization of the verses of the Qur'an at MI Faqihul Ilmi. This study uses a qualitative approach with a descriptive method. Data were obtained through observation, interviews, and documentation of students and educators at MI Faqihul Ilmi. The results of the study showed that the application of mind mapping can improve students' understanding and memory of the verses of the Qur'an. By using a combination of colors, images, and relationships between concepts, students find it easier to memorize and understand the meaning of the verses being studied. In addition, this method also increases students' learning motivation because it is more interactive than conventional memorization methods. The results of this study indicate that the use of mind mapping in learning to memorize the Qur'an at MI Faqihul Ilmi has a positive impact on the effectiveness of student memorization. Therefore, this method is recommended to be applied more widely in learning the Qur'an, both at the MI level and other Islamic educational institutions. Further research can be conducted to examine the effectiveness of this method in the long term and its application in various levels of education.